Fernando Carmona, Guillermo Montaño, Jorge Carrión y Alonso Aguilar M., El milagro mexicano. México, Editorial Nuestro Tiempo, 1970, 363 p. - García Rocha, Adalberto (Estudios Demográficos y Urbanos, 1971)
FERNANDO CARMONA, GUILLERMO MONTANO, JORGE CARRIÓN y ALONSO AGUILAR M., El milagro mexicano. México, Editorial Nuestro Tiempo, 1970.